A 24‐week study to evaluate the effect of rilapladib on cognition and cerebrospinal fluid biomarkers of Alzheimer's disease. Issue 2 (29th June 2015) - Maher‐Edwards, Gareth; De'Ath, Jeni; Barnett, Carly; Lavrov, Arseniy; Lockhart, Andrew
Abstract: Background: The lipoprotein‐associated phospholipase A2 inhibitor (Lp‐PLA2 ), rilapladib (SB659032), is being evaluated as a potential treatment to slow the progression of Alzheimer's disease (AD). Methods: One hundred twenty‐four subjects with possible mild AD and with neuroimaging evidence of cerebrovascular disease were randomized to placebo or 250‐mg rilapladib once daily, for 24 weeks, in addition to stable background acetylcholinesterase inhibitor and/or memantine. The study assessed the safety and tolerability of rilapladib and its effects on cognition, mechanistic, and disease‐related biomarkers. Although the overall intent behind the study was to take a broad exploratory view of the data, two primary end points of interest (cerebrospinal fluid [CSF] amyloid beta peptide 1–42 [Aβ1–42 ] and CogState executive function/working memory [EF/WM] composite score at week 24) were prespecified in the analysis plan for inferential statistical analysis. Results: Rilapladib was well tolerated with no significant safety concerns. A significant difference from placebo was observed for rilapladib on change from baseline in EF/WM (effect size, 0.45; P  = .026). There was no significant difference between groups on the change from baseline in CSF Aβ1–42 ( P  = .133). Preliminary evidence of effects was detected on other mechanistic (albumin quotient) and disease‐related biomarkers (tau/P‐tau and neurofilament light chain). Conclusion: These data provide initial evidence supporting Lp‐PLA2 inhibition as a novel treatment for dementia. Clinical Trial Registration: Clinicaltrials.gov identifier: NCT01428453 .